Women, Work and Fishing: An Examination of the Lives of Fisherwomen in Kerala - Lina Samuel (South Asia Research 2007; 27; 205, 2007)
This article focuses on women and their families in the fishing industry of Kerala, India. Documenting women's daily routines and experiences in their work, home and social circles, it reveals the continuing significance of social customs and traditions in limiting and confining women in their everyday life. Despite the varied roles that women play in the fishing industry, the income women earn from working has not altered pre-existing exploitative relations between men and women. Divisions based on caste, the emulation of upper caste behaviour, the continued practice and inflation of dowry, and traditional perceptions of women's responsibilities within the family combine to keep women in a secondary and subservient position relative to men